Effect of Coinfection by Fasciola hepatica and Mycobacterium bovis on Bovine Tuberculosis Immunodiagnosis in an Enzootic Area Hidalgo State, Mexico. - García-López Xitli; Jaramillo-Meza Laura; Quiroz-Romero Héctor; Arriaga-Díaz Camila; Martínez-Maya J. Juan; Diosdado-Vargas Fernando; Díaz-Otero Fernando (Journal of Veterinary Healthcare, 2018)
Parasitic infection by the Fasciola hepatica (F. hepatica) promotes susceptibility towards other infections, such as Mycobacterium bovis. As consequence, could affect diagnostic tests for this disease. Hence, the objective of this study was to assess the impact of F. hepatica coinfection on the most commonly used immunodiagnostic bovine tuberculosis (bTB) tests in field conditions in an enzootic area for both diseases. Thus, from a dairy herd located in Hidalgo State, México, displaying a 59.2% and 28% prevalence of fascioliasis and bTB, respectively. Sixty-one cows were analyzed based on their response towards bTB immunodiagnostic tests, such as Single Intradermal Comparative Tuberculin Test (SICTT), gamma-interferon test (BOVIGAM) and enzyme-linked immunosorbent assay (ELISA), along with the assessment of the F. hepatica parasite load and serodiagnosis by ELISA. Three study groups were formed according to test results. Group 1: coinfected (n=22). Group 2: non-parasitized cows, and positive for bTB tests (n=13) and Group 3: parasitized cows without tuberculosis (n=26). In addition, a group of cows kept in fascioliasis - and tuberculosis-free zones were included (Group 4, n=10). A non-parametric Kruskal-Wallis test and a Dunn test were applied to analyze the results. In Group 1, significant differences were observed regarding IFN-γ production, but not for antibody levels to M. bovis or reactivity towards bovine PPD in relation Group 2. While, Groups 1 and 3 did not display difference in antibody levels against F. hepatica. Differences were observed regarding tuberculosis and Fasciola diagnostic tests when both coinfected and infected groups were compared to controls. It is concluded that F. hepatica coinfection in tuberculous animals studied, depressed the production of IFN-γ towards bovine PPD under in vitro conditions, but its reactivity to the SICTT not show to be altered.
Keywords: Bovine tuberculosis